AUDIT TATA KELOLA TEKNOLOGI INFORMASI DI RSUD X MENGGUNAKAN FRAMEWORK COBIT 2019 - I Komang Satria Wibawa; Anak Agung Ngurah Hary Susila; Ni Made Ika Marini Mandenni (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
An IT governance audit at X Hospital was conducted due to various issues affecting service quality and system performance. Critical points included an overloaded database that resulted in suboptimal website information updates, inadequate server specifications to run the website when users were active, poorly managed network cables that made the server vulnerable to disruptions, and an under-protected IT unit in website management. The study aimed to identify critical points, elicit IT process capabilities, and provide improvement recommendations based on the COBIT 2019 Framework. The methods used included interviews, observations, business goal mapping and alignment, and a capability level questionnaire. The audit results identified five main domains, namely APO12, BAI10, DSS02, DSS03, and DSS04, all at capability level 2. Recommendations included IT risk integration, asset management, accelerated incident handling, improved service and satisfaction, and rapid adaptation to increase capabilities to levels 3, 4, and 5.